2016
DOI: 10.4155/fmc-2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Agents Targeting Ftsz Assembly

Abstract: Filamenting temperature-sensitive mutant Z (FtsZ), an essential cell division protein in bacteria, has recently emerged as an important and exploitable antibacterial target. Cytokinesis in bacteria is regulated by the assembly dynamics of this protein, which is ubiquitously present in eubacteria. The perturbation of FtsZ assembly has been found to have a deleterious effect on the cytokinetic machinery and, in turn, upon cell survival. FtsZ is highly conserved among prokaryotes, offering the possibility of broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 128 publications
0
29
0
Order By: Relevance
“…Other genes essential in both KIM1001 and CO92 which encode gene products unique to bacteria, such as the FtsZ cell division protein, the twin arginine transport (Tat) system and the SurA chaperone, encode potential drug targets. For example, currently there is significant interest in developing inhibitors of FtsZ [59]. Our study also identified novel targets for antimicrobial drugs including the hypothetical proteins YPO3498, YPO3579, YPO3586 and YPO3665/6/7 which encode the rod shape-determining proteins MreB, MreC and MreD respectively.…”
Section: Resultsmentioning
confidence: 82%
“…Other genes essential in both KIM1001 and CO92 which encode gene products unique to bacteria, such as the FtsZ cell division protein, the twin arginine transport (Tat) system and the SurA chaperone, encode potential drug targets. For example, currently there is significant interest in developing inhibitors of FtsZ [59]. Our study also identified novel targets for antimicrobial drugs including the hypothetical proteins YPO3498, YPO3579, YPO3586 and YPO3665/6/7 which encode the rod shape-determining proteins MreB, MreC and MreD respectively.…”
Section: Resultsmentioning
confidence: 82%
“…By using docking approaches, the authors suggest that their compounds might bind to the cell division protein FtsZ. Although these predictions are far away to be confirmed, anti‐FtsZ antimicrobials should constitute a novel group of antibiotics with clear clinical value (Panda et al, ).…”
Section: Commentarymentioning
confidence: 99%
“…The Z‐ring, along with other regulatory proteins, forms a divisome complex, which regulates membrane constriction and peptidoglycan synthesis . FtsZ plays a central role in bacterial division and its inhibition arrests the bacterial cell division establishing FtsZ as a potential antibacterial target . The increasing resistance of the microbes to the existing antibacterial agents urges for the discovery of antibacterial agents with novel drug targets.…”
Section: Introductionmentioning
confidence: 99%